Biocontrol of Important Pathogens of Forestry Species by Streptomyces Formulation - Dadwal, V. S.; , Jamaluddin (Indian Forester, 2003)
Streptomyces sp. was isolated from soil and was screened in the laboratory for antagonistic activity against pathogens of forest tree species viz. Alternaria alternata ,Curvularia lunata , Sarocladium oryzae , Fusarium oxysporum , Ganoderma lucidum and Macrophomina phaseolina. On basis of laboratory studies , it was also tried to control the seed microflora of Albizia lebbek. Suitable formulation was developed after growing Streptomyces sp. in seventeen different substrates. Farm yard manure and chicken manure were found as the best substrates and they were found as the best carrier for this biocide. Streptomyces sp. was also multiplied in bulk by using lab fermentar in liquid PDA medium. The inoculum in bulk was prepared by using farm yard manure as the carrier for field application. Post emergence damping off diseases of A. procera , A. lebbek and D. sissoo were also controlled. The growth and biomass of these species were also enhanced by treatment with Streptomyces sp. The trial of Streptomyces sp. to control sheath blight disease of D. asper also gave good performance by encouraging the healthy culms. Trials of Streptomyces sp. in the present study exhibited successful control of differcnt pathogens as compared with the fungicidal treatments. The use of this bioagent was bencficial from pesticidal residue problems and also to safe guard the soil in nurscry and plantations. It is a self-multiplying species of Streptomyces in soil , which is antagonistic to a number of soil borne pathogens. It appears a new species of Streptomyces. It can be concluded that this Streptomyces sp. can be used to control the different pathogen which are responsible for causing seed borne diseases , root diseases , damping off and leaf blight diseases in the nursery. The multilocational trials of the bulk cultures of this bioagent against root pathogens are under trials.